Ramadan di Berbagai Negara: Manifestasi Kebudayaan dalam Ibadah - Paramesthi, Amanda; Rahma, Ellana Ardelia Jovita; Syaifullah, Husen Indarno; Parhan, Muhamad (Peneliti.net, 2024)
Ramadan, the holy month in the Islamic calendar, is an important period commemorated by Muslims around the world as a month of fasting, prayer, reflection and community. Although the main events of Ramadan are fasting from dawn to dusk, increased worship and charity, remain unchanged, the cultural manifestations of Ramadan are diverse and reflect the rich local traditions of various countries. The aim of this research is to examine and compare Ramadan practices in different geographical and cultural contexts and to highlight how certain cultural elements are preserved, adapted or reinvented in the context of worship. By using a research type approach in the form of literature studies, this research reveals the uniqueness of Ramadan celebrations in several countries, such as Indonesia, Germany, and the United States. The results show that despite similarities in religious practices, local cultural differences influence the way food is prepared, Ramadan evening traditions are observed, and the organization of social activities, thereby adding to the richness and diversity of the Ramadan experience. This study provides insight into how Ramadan is not only a spiritual period, but also a moment when cultural and religious identities interact and strengthen each other, offering a new perspective on the dynamics between religion and culture in different global contexts.